Musculoskeletal symptoms among cleaners in Health Campus, USM - Noor, Nurhafezah Mohamed (Pusat Pengajian Sains Kesihatan, 2014)
This study was conducted to investigate the musculoskeletal symptoms among cleaners at Health Campus, USM. The muscular aches, pain and discomfort on part of the body can affect and disrupt the job performance. Physical, physiological and psychosocial factors are associated with MSDs among cleaners. The associations were identified by using chisquare test. The information about this study was collected through distribution of questionnaires to 112 respondents with guidance from the researcher. Observation of cleaning job was also conducted. Results from this study show female workers were dominated the cleaning job at Health Campus. The study also found that the body part that often experience muscular aches, pain and discomfort in the last 12 months were at the knee (69%), right wrist/hand (65%), upper back (68%), lower back (58%), legs (67%), and both the right and left shoulders (66% and 64%). The prevalence of location of muscular aches, pain and discomfort was similar with previous studies except for knees and foot. Pain in knees and foot can be associated with other risk factors of MSDs which is physiological (age) and psychosocial (lifestyle and diet). Relationship between musculoskeletal symptom with physical, personal and psychosocial risk factors were identified. For physical factors, work task that associated with risk of MSDs was mopping and moving furniture whereas personal factor were gender and age. Psychosocial factor which is work organisation (helps from others, work intensity, time to complete all works and controls on deciding own break) and job location also have association with the risk of MSDs among cleaners at Health Campus. As a conclusion, the- presence of musculoskeletal symptoms among cleaning workers in Health Campus should be considered by the management as well as the individual because it involves quality of life of the workers and the companies’ reputations.